PERENCANAAN COLD STORAGE SEBAGAI PENYIMPANAN UDANG VANAME DAERAH DI KABUPATEN POHUWATO PROVINSI GORONTALO - Pido, Rifaldo; Gobel, Fendy Faizal; Edahwati, Luluk (Universitas Bina Taruna Gorontalo, 2023)
This study describes the calculation of cold storage analysis for planning the preservation of vannamei shrimp in Pohuwato Regency. The purpose of this paper is to calculate the cooling load on frozen fish cold storage, calculate the performance of the vapor compression cycle including mass flow rate, compressor power, and COP. This study uses a theoretical design method. Cold storage design for product storage. The design data was obtained from field observations. The calculation results showed that the Refrigerant used was Refrigerant 12 (R-12), a vannamei shrimp product. The cycle cooling load is 47.33 kW. Cold storage designed for the process of preserving shrimp with a capacity of 13 tons, Cooling temperature in cold storage is 10° C, Superheated temperature is 5° C, Sub cooled temperature is 5° C, Refrigerant temperature in the condenser is 35° C, Refrigerant temperature in the evaporator is 5° C, the pressure in the condenser is 0.8 MPa, the pressure in the evaporator is 0.4 MPa so that a coefficient of performance (COP) of 4.7 is obtained.